The assessment of quality maturity levels in Nigerian university libraries. Issue 6 (5th September 2017) - Egberongbe, Halima; Sen, Barbara; Willett, Peter
Abstract : Purpose: Organizations constantly evaluate their activities to ensure that they are attaining their management goals. Maturity assessment enables organizations to examine their capabilities, support innovation and evaluate development. The aim of this paper is to evaluate the maturity statuses of a selection of Nigerian university libraries in a study to investigate their quality management (QM) approaches. The study provides recommendations for means to attain the required statuses in academic library development. Design/methodology/approach: The study involved a multisite case study in which interviews were conducted with 15 university librarians (or their representatives) and ten focus groups were conducted with non-management library staff. The resulting qualitative data were analyzed using an aspect of framework analysis – charting, while a maturity model from the field of project management (Prince 2 Maturity Model, P2MM) was used to assess maturity in QM of the libraries. Findings: The results of the maturity assessment indicate a basic knowledge of the concept of QM implementation among the libraries. The scores obtained on the P2MM capability scale placed the libraries studied mainly on Level 1 (awareness level) of the model. Practical implications: This paper demonstrates that the culture of QM in academic libraries in Nigeria is at a low level with considerable potential for development. It is suggested that future adoption of quality maturity models to assess performance and organizational effectiveness would aid improvements for value-added services. Originality/value: This is the first study to attempt the assessment of quality maturity levels in Nigerian academic libraries for identification of the organization's positioning in QM and strategy.